2005
DOI: 10.1002/ajim.20176
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin exposure and symptoms in wastewater treatment workers

Abstract: Wastewater treatment workers reported a wide range of symptoms that may be work-related. Microbial exposures such as endotoxin seem to play a causal role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 29 publications
4
64
2
Order By: Relevance
“…A significantly increased risk for chronic bronchitis and pneumonia has been reported for sewage workers, [11][12][13][14] and possible causative agents include viruses, other microorganisms, and endotoxins. [14][15][16] Smit et al 17 even reported a dose-response relationship between endotoxin exposures and flu-like symptoms. Chemical irritants such as lime, ammonia, and alkyl amines also may contribute to broncho-obstructive and inflammatory responses.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly increased risk for chronic bronchitis and pneumonia has been reported for sewage workers, [11][12][13][14] and possible causative agents include viruses, other microorganisms, and endotoxins. [14][15][16] Smit et al 17 even reported a dose-response relationship between endotoxin exposures and flu-like symptoms. Chemical irritants such as lime, ammonia, and alkyl amines also may contribute to broncho-obstructive and inflammatory responses.…”
Section: Commentmentioning
confidence: 99%
“…An increased risk for central nervous symptoms such as unusual tiredness has been reported among sewage workers 15,17 and among persons in an organic dust environment. 25 We observed an increased risk for arthritis and osteoarthritis in this study.…”
Section: Commentmentioning
confidence: 99%
“…The study was approved by the Bioethical Committee, Military Institute of Medicine, Warszawa, Poland. increased risk of irritation of the respiratory system, eyes, and skin as well as the neurological and gastric symptoms among sewage workers and landfill workers [18][19]. The upper respiratory tract with the olfactory and gustatory receptors is particularly exposed to the activity of hazardous agents.…”
Section: Discussionmentioning
confidence: 99%
“…This increased rate was found even at exposure to hydrogen sulphide below the level of 1 ppm, and endotoxins below 91 units per m 3 (EU/m 3 ). Smit et al [18] observed an increased frequency of health problems under conditions of endotoxin exposure above the level of 50 U/m 3 . The technological development and progress in occupational medicine makes it possible to monitor and limit occupational exposure to chemical and biological hazards, thus diminishing their influence on workers' health [25].…”
Section: Taste and Smell Perception Among Sewage Workers O R I G I N mentioning
confidence: 99%
See 1 more Smart Citation